ACTH Enhances Lipid Accumulation in Bone-marrow derived Mesenchymal Stem Cells undergoing Adipogenesis - Rhodes, Thomas J.; Pazienza, Michelle; Evans, Jodi F. (Journal of Student Research, 2015)
ACTH is a major hormone of the stress axis or hypothalamic-pituitary-adrenal (HPA) axis. It is derived from pro-opiomelanocortin (POMC) the precursor to the melanocortin family of peptides. POMC produces the biologically active melanocortin peptides via a series of enzymatic steps in a tissue-specific manner, yielding the melanocyte-stimulating hormones (MSHs), corticotrophin (ACTH) and ?-endorphin. The melanocortin system plays an imperative role in energy expenditure, insulin release and insulin sensitivity. Bone marrow derived mesenchymal stem cells circulate in the blood stream and as progenitor cells have the potential to differentiate into many cell types such as osteoblasts, chondrocytes and adipocytes. Here we examine the effects of ACTH on the mouse D1 bone-marrow derived MSC. ACTH significantly increased lipid accumulation during the adipogenic differentiation of D1 cells in a concentration- dependent manner. ACTH also shifts the temporal pattern of D1 adipogenic differentiation to the left i.e. differentiation occurs earlier with ACTH treatment. No significant differences in protein expression of peroxisome proliferator-activated receptor gamma (PPAR-?2), a regulating transcription factor of adipogenesis were found. Therefore the effects of ACTH are suggested to be mediated by an alternative pathway. Overall the results indicate a connection between increased adipose deposition and the elevated circulating ACTH associated with stress.